The Effect of Work Motivation and Disciplin on Performance of Palopo City Police Personnel - Yerlin Tandi Kate; M. Risal; Muhammad Aqsa (Jurnal Mantik, 2021)
The Research using multiple linear regression analysis is research that combines more than one independent variable. In this study the independent variables are Motivation and Work Discipline. This study tries to describe how and how much influence is given by the two independent variables on the performance of personnel in the Polres area of ??Palopo City. With a sample of 100 from four police stations in the Polopo Polres area. The research findings say that motivation and work discipline have a positive and partially significant effect. Simultaneously motivation and work discipline also affect the performance of personnel in the Polopo Polres area